Education, Business, and Information Technology: Building Innovative Ecosystems in the Midst of Disruption - Alingka Fahada Firmatasya; M. Mafatihul Falah Mz; Muhammad Amanulloh Mz; Mz, Nur Ismianah (GURUPEDIA: Journal of Teacher and Education, 2025)
The year 2025 will be a crucial point for Indonesia in facing interrelated cross-sectoral challenges, especially in the fields of education, business, and information technology. These three sectors play a strategic role in driving economic growth, strengthening human resources, and accelerating digital transformation. This research aims to identify the main challenges faced by each sector and analyze their linkages and impacts on national development. Using a descriptive qualitative approach, data was collected through literature studies, expert interviews, and policy analysis. The results show that education still faces access and quality gaps, businesses are under pressure due to digital disruption and market uncertainty, while the information technology sector faces challenges in terms of digital literacy, data security, and equitable distribution of infrastructure. This research emphasizes the importance of integrated cross-sector and policy collaboration to address these challenges holistically. Strategic recommendations are given to strengthen synergy between the world of education, business actors, and technology developers in building an inclusive, adaptive, and sustainable ecosystem.